A Laboratory Evaluation of Ammonia Volatilization and Nitrate Leaching following Nitrogen Fertilizer Application on a Coarse‐Textured Soil. (1st May 2015) - Peng, Xianlong; Maharjan, Bijesh; Yu, Cailian; Su, Anyu; Jin, Virginia; Ferguson, Richard B.
Abstract : In a series of field studies, differing rainfall patterns within the first month after N fertilizer application to a coarse‐textured soil significantly affected yields and N‐use efficiency of irrigated corn ( Zea mays L.), and responses varied with N source. A laboratory study was conducted to evaluate effects of N source with precipitation following N application to a coarse‐textured soil. Nitrogen sources included urea‐ammonium nitrate solution (UAN), UAN with additives of either nitrapyrin (2‐chloro‐6‐[trichloromethyl] pyridine) as a nitrification inhibitor or maleic‐itaconic acid copolymer as a urease and nitrification inhibitor, or polymer‐coated dry urea (PCU). These products were applied to soil in chambers from which ammonia (NH3 ) volatilization and nitrate (NO3 − ) leaching were measured over 31 d following fertilization. Precipitation events simulated rainfall frequencies and amounts that occurred in field studies in dry and wet conditions. Ammonia volatilization was lower in wet than dry conditions. Total NH3 loss for the dry precipitation regime ranged from 11 to 18% of applied N fertilizer for all treatments except PCU (<1%). In contrast, all treatments in wet conditions had low NH3 loss (<1% of applied N). However, substantial NO3 − leaching occurred with wet conditions, comprising 48 to 66% of applied N for most treatments. Leaching loss was the greatest for UAN, followed by UAN with additives. For either dry or wet environments, losses of N from PCU to either NH3 volatilization or NO3 − leaching were negligible.